The Politics of Faith and the Limits of Scientific Reason: Tracking the Anthropology of Human Rights and Religion - Clarke, Kamari Maxine (Religion and society, 2010)
This article explores the reality of translating or vernacularizing practices in relation to the politics of religion and the realities of faith. Taking violence as endemic to the processes of vernacularization and translation, the article articulates an analytic theory of religious faith—the way it is violated, often in the interest of making it legible within neo-liberal universalizing trends. Thinking about these realities involves understanding translations both as productive of cultural change and as manifestations of struggles over power. Many of these struggles are in the interstices among particular principles of individualism, secularism, legal rationality, and evidence. This article seeks to review the assumptions that emerge with these concepts and show their limits.